2023
DOI: 10.3389/fonc.2023.1024151
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic reprogramming in pancreatic premalignancy and clinical implications

Abstract: Pancreatic cancer (PC) is the most lethal human cancer, with less than 10% 5-year survival. Pancreatic premalignancy is a genetic and epigenomic disease and is linked to PC initiation. Pancreatic premalignant lesions include pancreatic intraepithelial neoplasia (PanIN), intraductal papillary mucinous neoplasm (IPMN), and mucinous cystic neoplasm (MCN), with pancreatic acinar-to-ductal metaplasia (ADM) as the major source of pancreatic premalignant lesions. Emerging evidence reveals that an epigenetic dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 155 publications
(183 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, miR-483-3p is upregulated in PanIN, and its expression levels correlate with the progression of PanIN. Notably, circulating levels of miR-483-3p are significantly elevated in the serum and serum exosomes of patients with PC, confirming the evidence demonstrated by Abue et al Interestingly, serum levels of miR-483-3p were shown to be able to effectively differentiate between patients with early stage PC (≤ 2 cm) and healthy controls [ 139 ]. Finally, a targeted study of exosomal miRNA profiles in early lesions and cancer showed differential expression of miRNA-196b-3p and miRNA-204-3p between IPNM, MCN and PC.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Furthermore, miR-483-3p is upregulated in PanIN, and its expression levels correlate with the progression of PanIN. Notably, circulating levels of miR-483-3p are significantly elevated in the serum and serum exosomes of patients with PC, confirming the evidence demonstrated by Abue et al Interestingly, serum levels of miR-483-3p were shown to be able to effectively differentiate between patients with early stage PC (≤ 2 cm) and healthy controls [ 139 ]. Finally, a targeted study of exosomal miRNA profiles in early lesions and cancer showed differential expression of miRNA-196b-3p and miRNA-204-3p between IPNM, MCN and PC.…”
Section: Introductionsupporting
confidence: 73%
“…Other nucleic acids that are proving to be interesting biomarkers include circulating microRNA and lncRNA, which are tumor (and PC) specific and can be easily detected in the circulation of patients as potential diagnostic biomarkers of malignancy [ 138 ]. Even if the study of miRNA deregulation was well characterized as a very early event in the progression of PC and several miRNAs were identified to be involved in PanIN, IPMN and MCM progression, only a few of them were applied stepwise as biomarkers in plasma patients [ 139 ]. Interestingly, Lui J and colleagues evaluated the possibility of combining the plasma miRNA dosage with the early detection of CA-19–9, and claimed that the combination of CA19-9, miR-16, and miR-196a in the plasma is more effective in distinguishing PC from non-PC patients (normal or chronic pancreatitis), especially in early tumor screening [ 130 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation